Certain integral operator and strongly starlike functions - Jin-Lin Liu (International Journal of Mathematics and Mathematical Sciences)
Let S∗(ρ,γ) denote the class of strongly starlike functions of order ρ and type γ and let C(ρ,γ) be the class of strongly convex functions of order ρ and type γ. By making use of an integral operator defined by Jung et al. (1993), we introduce two novel families of strongly starlike functions Sβα(ρ,γ) and Cβα(ρ,γ). Some properties of these classes are discussed.